Unravel Persistent Land Tenure Insecurity Behind Indonesia’s Palm Oil Industry: Study case Kinipan Indigenous Community in Central Kalimantan. - Tuslian, Widya Naseva (UI Scholars Hub, 2021)
This paper argues that legal pluralism within the context of state law contributes to tenure insecurity experienced by indigenous communities behind the palm oil industry in Indonesia. The palm oil industry is an industry that contributes significantly to Indonesia's economy and is a mainstay of national export. However, this industry is also renowned for bringing multidimensional issues such as ecological problems, biodiversity crises, and land conflict with existing inhabitants, particularly indigenous groups. The latter issue is peculiar in Indonesia's palm oil industries as, in many cases, palm oil projects overlapped with indigenous people's forest land or places where they reside. Moreover, talking about the land rights of an indigenous group in Indonesia, especially in the context of palm oil sectors, will always involve various state legal norms and institutions, which, unfortunately, in most cases render uncertainty which is harmful to indigenous people's tenure security. This paper also put forward that the law-making process that primarily holds up economic rationality and favors large palm oil corporations results in various contradicted legal products that are detrimental to the acknowledgement of indigenous community's existence and their land rights. Taking the Kinipan Indigenous group in Central Kalimantan as a case study, this paper primarily discusses the general pattern of tenure insecurity experienced by the Indigenous community in Indonesia in facing the large-scale palm oil corporations.